EPO and doping - Balestra, C.; Germonpre, P. (European Journal of Applied Physiology, 2010)
Hypoxia is not the only trigger for increasing EPO. Relatively short periods of oxygen breathing are likewise capable of producing this effect. Competitive breathhold diving has the greatest potential for increasing EPO levels. Yet, this does not achieve potential harmful levels of haemoglobin while affording the individuals with some neuroprotective effects. Accordingly, the rationale for inducing EPO through prior oxygen breathing for a limited period may be entirely appropriate . It is interesting to note that elevated plasma EPO levels do not increase breathholding time. Therefore, this does not result in a doping effect. Therefore, we thoroughly concur with Guido Ferretti who argues against considering intermittent hypoxia as a doping procedure.